Allografts of tumor nuclear transplantation embryos: differentiation competence. - Lust, J M (1991)
The developmental potential of nuclei can be studied by nuclear transplantation. Although amphibian blastula nuclei and other early embryonic nuclei are totipotent, to our knowledge no nucleus from an adult cell has ever been shown to be totipotent by this procedure. Transfer of Lucké renal carcinoma nuclei into enucleated eggs results in prefeeding swimming tadpoles. Inasmuch as these tadpoles die, rescue of this pluripotential tissue was attempted by grafting fragments of triploid tumor nuclear transplant tadpoles to the tails of normal diploid Rana pipiens hosts. Grafts of tumor nuclear transplant tadpole tissue were histologically indistinguishable from grafts of normally fertilized embryos and developed normal-appearing structures such as complete eyes, well-differentiated neural tissues, kidney tubules, and gut epithelium. Moreover, histological differentiation in tumor nuclear transplant grafts was comparable to that observed in 50-day-old normal larvae. Grafting enhanced the survival of tumor nuclear transplant tissue from no more than 14 days as part of the donor tadpole to 40 days at which time the grafts were harvested as healthy tissue. Thus, both differentiation and survival of tumor nuclear transplant tissue were augmented with the grafting procedure. Cytophotometric analysis of ploidy was used to confirm the tumor origin of the donor tissue.